2013
DOI: 10.3329/jdmc.v21i2.15358
|View full text |Cite
|
Sign up to set email alerts
|

Study on Effects of Wheatgrass (Triticum aestivum) Juice on Serum Triglyceride of Experimentally Induced Hypercholesterolaemic Male Long Evans Rat

Abstract: J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 197-203 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15358

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It indicates preventive role of grass juice against hypercholesterolaemia. Moreover, similar lipid lowering effects of wheat grass juice were evident in case of cholesterol 16 and triglyceride 17 as per experiments done in the same set up. However, the lipid lowering effect of grass juice in the present study was found to be dose dependant.…”
Section: Discussionsupporting
confidence: 79%
“…It indicates preventive role of grass juice against hypercholesterolaemia. Moreover, similar lipid lowering effects of wheat grass juice were evident in case of cholesterol 16 and triglyceride 17 as per experiments done in the same set up. However, the lipid lowering effect of grass juice in the present study was found to be dose dependant.…”
Section: Discussionsupporting
confidence: 79%
“…The rats were divided into eight groups for the study. The study showed that a group of rats taking wheatgrass juice daily showed a significant reduction in serum triglycerides, thus indicating a preventive role of wheatgrass juice against increased levels of triglycerides in the blood [46].…”
Section: Effect Of Wheatgrass In Lowering Cholesterolmentioning
confidence: 91%
“…Then 10 gm cholesterol was dissolved in olive oil to make it 1 liter solution which was equivalent to 1% cholesterol in olive oil and it was used as high cholesterol diet. Around 1.5 ml solution of High cholesterol diet was given to rats per day to render them hyperlipidemic 11 . Experimental I: Effect of Glycine max (GM) extract on serum lipid profile in normal rats.…”
Section: High Cholesterol Diet (Hcd)mentioning
confidence: 99%